Virulensi beberapa isolat Pantoea ananatis penyebab penyakit hawar daun bakteri (bacterial leaf blight) pada varietas bawang merah - Asrul Asrul (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Bacterial leaf blight caused by Pantoea ananatis in onions is a new disease in Indonesia. Information regarding the level of virulence of these pathogens in onion plants is unknown. This study aims to determine the level of virulence of P. ananatis isolates in onion plants originating from Cirebon, Tegal, Nganjuk, Bantul, and Sigi districts. The study was conducted by an experimental method using 150 pathogen isolates and 4 onion cultivars in a greenhouse from 5 regions. Experimental data were analyzed descriptively with the help of image and table views. The results showed that all pathogenic isolates had the same level of virulence (uniform) and were very virulent against 4 cultivars of obese bima, blue rice fields, bauji, and palasa. All of these isolates gave the same response to the fast incubation period (2.35 - 2.90 days), the percentage of leaves that were heavily attacked (67.44 - 81.76%), and a high infection rate (> 0.5 units per day).